2015
DOI: 10.1007/s10753-015-0144-y
|View full text |Cite
|
Sign up to set email alerts
|

Cyanidin-3-O-Glucoside Ameliorates Lipopolysaccharide-Induced Injury Both In Vivo and In Vitro Suppression of NF-κB and MAPK Pathways

Abstract: Cyanidin-3-O-glucoside (C3G), an anthocyanin belonging to the flavonoid family and commonly present in food and vegetables in human diet, has exhibited anti-inflammatory and anti-oxidant effects. This study aimed to investigate the protective ability of C3G against inflammatory and oxidative injuries, as well as to clarify the possible mechanism in lipopolysaccharide (LPS)-stimulated human umbilical vein endothelial cells (HUVECs) in vitro and acute respiratory distress syndrome mouse model in vivo. HUVECs or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 31 publications
2
44
0
Order By: Relevance
“…However, the specific role and mechanisms of action of C3G, the most widely distributed anthocyanin monomer (Figure A), in protecting HDFs from UVA damage has remained unclear. Recently, it was demonstrated that C3G reduces oxidative damage and regulates MAPK pathways in UVB‐induced damage in retinal pigment epithelial cells and lipopolysaccharide (LPS)‐stimulated human umbilical vein endothelial cells . Therefore, we hypothesized that C3G could be a useful compound for preventing and improving UV‐induced skin injury due to its antioxidant properties and ability to regulate MAPK pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the specific role and mechanisms of action of C3G, the most widely distributed anthocyanin monomer (Figure A), in protecting HDFs from UVA damage has remained unclear. Recently, it was demonstrated that C3G reduces oxidative damage and regulates MAPK pathways in UVB‐induced damage in retinal pigment epithelial cells and lipopolysaccharide (LPS)‐stimulated human umbilical vein endothelial cells . Therefore, we hypothesized that C3G could be a useful compound for preventing and improving UV‐induced skin injury due to its antioxidant properties and ability to regulate MAPK pathways.…”
Section: Discussionmentioning
confidence: 99%
“…19 However, the specific role and mechanisms of action of C3G, the most widely distributed anthocyanin monomer 13 (Figure 2A 20 and lipopolysaccharide (LPS)-stimulated human umbilical vein endothelial cells. 21 Therefore, we hypothesized that C3G could be a useful compound for preventing and improving UV-induced skin injury due to its antioxidant properties and ability to regulate MAPK pathways.…”
Section: Discussionmentioning
confidence: 99%
“…These findings give further evidence that nongenomic function of Nur77, such as protein-protein interactions, may contribute to the downregulation of LPS-induced ET-1 expression. Activation of NF-κB p65 and p38 MAPK is involved in the pathogenesis of ARDS through inducing proinflammatory mediators expression (30, 47, 100), one of which is ET-1.…”
Section: Discussionmentioning
confidence: 99%
“…Anthocyanins are water‐soluble vacuolar pigments found in most species in the plant kingdom and are responsible for the red, purple, and blue colors of many fruits, vegetables, and flowers (Jing et al., ), and exhibit potential free radical‐scavenging activities that prevent low‐density lipoprotein oxidation and positively effect on chronic gut inflammatory diseases, obesity, and inflammation (Cuevas‐Rodríguez, Dia, Yousef, Garcia‐Saucedo, & Lopez‐Medina, ; Fernandes et al., ; Lin, Fischer, & Wicker, ; Sousa et al., ). C3G, which is an anthocyanin with a high percentage and belongs to the flavonoid family and commonly present in the human diet, exhibits anti‐inflammatory and antioxidant effects (Cai et al., ; Jung, Kwak, & Hwang, ; Ma et al., ). Studies have showed that C3G protects from the adverse effects of radiation, controls the key aspects of tumorigenesis, inhibits proliferation, induces apoptosis of cancer cells, reduces oxidative stress, fights H 2 O 2 ‐induced oxidative stress in human embryonic kidney cells, induces cell apoptosis and inhibits cell migration (Lee et al., ; Pratheeshkumar et al., ; Priego et al., ; Yan et al., ).…”
Section: Introductionmentioning
confidence: 99%